PARTITION AS BORDER-MAKING - Ferdous, Sayeed. ([S.l.])
1 online resource
Keywords: This book critically analyzes the Partition experiences from East Bengal in 1947 and its prolonged aftermath leading to the creation of Bangladesh in 1971. It looks at how newly emerged borderlands at the time of Partition affected lives and triggered prolonged consequences for the people living in East Bengal/Bangladesh. The author brings to the fore unheard voices and unexplored narratives, especially those relating the experience of different groups of Muslims in the midst of the falling apart of the unified Muslim identity. Drawing on in-depth ethnographic research and archival resources, the volume analyzes various themes such as partition literature, local narratives of border-making, smuggling, border violence, refugees, identity conflicts, border crossing, and experiences of the Bihari Muslims and the Hindus of East Pakistan, among others. A unique study in border-making, this book will be an essential read for scholars and researchers of history, South Asian history, Partition studies, oral history, anthropology, political history, refugee studies, minority studies, political science, and borderland studies.